(untitled) (diségno, 2019)
The paper aims to highlight the potential and applicability of an integrated digital approach that uses the drawing as a concrete tool in support of the territorial and urban design. The integration of territorial analysis tools, together with others more traditionally used in algorithmic-generative processes, could allow to reach a global management system of data and information. In fact, territorial and urban transformations, by their nature or by virtue of their intrinsic complexity, require multi-scale control and managed on multiple interconnected levels. Through specific digital representations, we intend to illustrate the possibility of using a GIS system, integrated with parametric mod- ellers, for the management and verification of a series of design choices that involve urban or territorial transformations. The proposed methodology aims to validate an analysis system applicable whenever actions are needed within an already consolidated urban space, especially to create or implement linear networks. The proposed operating procedure is therefore aimed at identifying cycle paths through a semiautomatic framework: the contribution proposes, in particular, an application on the road network of the Capaccio-Paestum Municipality, in the province of Salerno.